An assessment of a 3D EPID-based dosimetry system using conventional two- and three-dimensional detectors for VMAT. (January 2018) - Stevens, S.; Dvorak, P.; Spevacek, V.; Pilarova, K.; Bray-Parry, M.; Gesner, J.; Richmond, A.
Highlights: Validation of EPID pre-treatment & transit dose using 2D and 3D detectors. Direct comparison between EPID pre-treatment, transit, 2D/3D detectors. Validation indicates achievable gamma index under ideal conditions. In-house gamma methodology ensures consistency for 2D and 3D modalities. Abstract: Purpose: To provide a 3D dosimetric evaluation of a commercial portal dosimetry system using 2D/3D detectors under ideal conditions using VMAT. Methods: A 2D ion chamber array, radiochromic film and gel dosimeter were utilised to provide a dosimetric evaluation of transit phantom and pre-treatment 'fluence' EPID back-projected dose distributions for a standard VMAT plan. In-house 2D and 3D gamma methods compared pass statistics relative to each dosimeter and TPS dose distributions. Results: Fluence mode and transit EPID dose distributions back-projected onto phantom geometry produced 2D gamma pass rates in excess of 97% relative to other tested detectors and exported TPS dose planes when a 3%, 3 mm global gamma criterion was applied. Use of a gel dosimeter within a glass vial allowed comparison of measured 3D dose distributions versus EPID 3D dose and TPS calculated distributions. 3D gamma comparisons between modalities at 3%, 3 mm gave pass rates in excess of 92%. Use of fluence mode was indicative of transit results under ideal conditions with slightly reduced dose definition. Conclusions: 3D EPID back projected dose distributions were validated against detectors in both 2D and 3D. Cross validation of transit dose delivered to a patient is limited due to reasons of practicality and the tests presented are recommended as a guideline for 3D EPID dosimetry commissioning; allowing direct comparison between detector, TPS, fluence and transit modes. The results indicate achievable gamma scores for a complex VMAT plan in a homogenous phantom geometry and contributes to growing experience of 3D EPID dosimetry.